Transformational Leadership and Educational Quality Management Implementation in Primary Schools: Kepemimpinan Transformasional dan Implementasi Manajemen Mutu Pendidikan di Sekolah Dasar - Widyawati, Ni Komang Windi; Rizal, Rizal; Pahriadi, Pahriadi; Nashrullah, Nashrullah; Mas'adi, Mas'adi; Bulalong, Roberto Rolly (Academia Open, 2026)
General Background In the globalization era, academic systems must continuously adapt to develop competent human resources through comprehensive administration. Specific Background At the basic education level, principals hold essential responsibilities in mobilizing staff and creating collaborative work environments to achieve national learning goals. Knowledge Gap Despite the acknowledged importance of school headship, empirical investigations detailing specific strategies to overcome limited staff participation in decision-making and fragmented program coordination remain necessary. Aims This study investigates how the principal applies transformational approaches to govern institutional standards at SD Inpres Mantawa B. Results Utilizing a qualitative descriptive approach with interviews, questionnaires, and documentation, findings reveal that the principal successfully applied idealized influence and inspirational motivation. Teachers were actively integrated into vision formulation and program planning, while professional development was supported through training and working groups. Quantitative survey data confirmed this success, yielding a score of 78.09%, categorizing the administrative performance as good. Novelty This research isolates the dual function of this specific leadership style in mitigating administrative burdens while directly cultivating a participatory culture among teaching staff. Implications Transformational approaches serve as a sustainable framework for basic education institutions to systematically elevate institutional standards, strengthen staff commitment, and resolve structural coordination challenges. Highlights The principal integrated teachers into vision formulation and program planning processes. Quantitative survey data categorized the administrative performance at a good level. Idealized influence alongside inspirational motivation resolved fragmented coordination challenges. Keywords Transformational Leadership; Quality Management; Primary Education; Teacher Commitment; Educational Administration